THE DEVELOPMENT OF TRADITIONAL ROMANIAN FOOD PRODUCTS - Elena NECULCEA; Ion DONA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Traditional products preserve and promote local identity, culture and tradition. They also contribute to the local economy, environmental protection and public health. This paper studied the development of the traditional products sector in Romania in the period 2013-2022. The main objective was to show the distribution among product types and landforms. The information was gathered from two main sources, the “National Register of Traditional Products” and the “Catalogue of Certified Products and Activities” of the Romanian Ministry of Agriculture, Forestry and Rural Development. The research showed that almost 41.6% of traditional products are found in the meat and meat products category, followed by milk and dairy products with 18.2%. They are mainly produced in mountain and lowland areas. In the period 2013-2022, an increase in product structure can be observed in beverages and bakery products in lowland areas, vegetable and fruit products in mountain areas, and fish products in mountain areas.